Quantum Learning Model Using Miniature Terrarium Media to Improve Science Learning Outcomes on Ecosystem Material in Grade V of SD Negeri 104202 Bandar Setiabudi (International Journal of Education and Literature, 2025)
This study aims to analyze the effect of the Quantum Learning model using miniature terrarium media to improve science learning outcomes in grade V of SD Negeri 104202 Bandar Setia. The type of research used is a pre-experimental method with a One Group Pretest-Posttest design . The subjects in this study were 21 students in class VC who were determined through non-probability sampling techniques. The test instrument was in the form of 20 multiple-choice questions that had been analyzed through validity and reliability tests. The data results were analyzed using normality, homogeneity, linearity, simple linear regression, and paired sample t-test tests . The results showed that the average pre-test score was 68.57, increasing to 87.14 in the post-test. The paired sample t-test produced a Sig. value. 0.000 < 0.05 so that H0 is rejected and H1 is accepted, while the regression test obtained an R (R Square) of 0.691, which means that the Quantum Learning model with miniature terrarium media has an effect of 69.1% on improving student learning outcomes. This finding confirms that the Quantum Learning model using terrarium media has an effect on improving student learning outcomes.